Role of microRNAs involved in plant response to nitrogen and phosphorous limiting conditions - Nguyen, Giao; Rothstein, Steven; Spangenberg, German; Kant, Surya (Frontiers in Plant Science, 2015)
Plant microRNAs (miRNAs) are a class of small non-coding RNAs which target and regulate the expression of genes involved in several growth, development, and metabolism processes. Recent researches have shown involvement of miRNAs in the regulation of uptake and utilization of nitrogen (N) and phosphorus (P) and more importantly for plant adaptation to N and P limitation conditions by modifications in plant growth, phenology, and architecture and production of secondary metabolites. Developing strategies that allow for the higher efficiency of using both N and P fertilizers in crop production is important for economic and environmental benefits. Improved crop varieties with better adaptation to N and P limiting conditions could be a key approach to achieve this effectively. Furthermore, understanding on the interactions between N and P uptake and use and their regulation is important for the maintenance of nutrient homeostasis in plants. This review describes the possible functions of different miRNAs and their cross-talk relevant to the plant adaptive responses to N and P limiting conditions. In addition, a comprehensive understanding of these processes at molecular level and importance of biological adaptation for improved N and P use efficiency is discussed.